2018
DOI: 10.15366/rimcafd2018.69.008
|View full text |Cite
|
Sign up to set email alerts
|

Versión española de la escala de necesidades psicológicas básicas en educación física / Spanish Version Of The Basic Psychological Needs In Physical Education Scale

Abstract: RESUMEN La Escala de Necesidades Psicológicas Básicas en Educación Física (BPN-PE), una versión modificada de la exitosa Escala de las NecesidadesPsicológicas Básicas en el Ejercicio (BPNES) fue diseñada para desarrollar una herramienta específica que midiera estas necesidades en la educación física. El objetivo del presente estudio fue validar esta escala al contexto español. Participaron 624 estudiantes de educación secundaria y bachillerato (332 hombres y 292 mujeres) de ocho centros educativos diferentes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
1
5
0
6
Order By: Relevance
“…The Psychological Need Satisfaction in Exercise Scale [21] and the Basic Psychological Need Satisfaction Scale in Exercise [22], of which the latter one was validated and adapted for the PE context in Greek [23]. Containing 12 items, the BPNS-PE supported a three-factor structure and had high internal consistencies, which was recently confirmed by CFA in a Spanish [24] and English sample in PE [25]. Trigueros et al examined an adequate fit for a four-factor solution of the Spanish Scale of the Satisfaction of Psychological Needs in Physical Education [26], including a fourth subscale to assess the newly introduced need of novelty [27], and estimated an acceptable reliability by Cronbach's alpha of α > 0.70.…”
Section: Introductionmentioning
confidence: 84%
“…The Psychological Need Satisfaction in Exercise Scale [21] and the Basic Psychological Need Satisfaction Scale in Exercise [22], of which the latter one was validated and adapted for the PE context in Greek [23]. Containing 12 items, the BPNS-PE supported a three-factor structure and had high internal consistencies, which was recently confirmed by CFA in a Spanish [24] and English sample in PE [25]. Trigueros et al examined an adequate fit for a four-factor solution of the Spanish Scale of the Satisfaction of Psychological Needs in Physical Education [26], including a fourth subscale to assess the newly introduced need of novelty [27], and estimated an acceptable reliability by Cronbach's alpha of α > 0.70.…”
Section: Introductionmentioning
confidence: 84%
“…BPN satisfaction in PE. The Spanish version (Menéndez-Santurio & Fernández-Río, 2018) of the Basic Psychological Need in Physical Education Scale (Vlachopoulos et al, 2011) was used. The scale is preceded by the statement "In my PE classes .…”
Section: Instrumentsmentioning
confidence: 99%
“…Autonomy is understood as the desire to feel that one is the originator and regulator of one's own behavior, competence is the person's perception of being able to show effectiveness within a particular context and relatedness refers to the feeling of belonging to a social environment [29,31]. It has been shown that any element that can satisfy basic psychological needs will lead to improvements in intrinsic and self-determined motivation of the individual, as well as to greater enjoyment of physical education classes [32]. Finally, cooperative learning has gained great importance in recent years, especially in the field of education, and is considered as a methodological tool that can help to meet the needs of 21st-century students [33].…”
Section: Introductionmentioning
confidence: 99%